A Demanding Ethics of Care - Kittay, Eva Feder (The Hastings Center report, 2020)
The writer responds to the book review essay “Caring for People with Disabilities: An Ethics of Respect,” by Kevin Mintz and David Wasserman, in the January-February 2020 issue of the Hastings Center Report, which discusses her book Learning from My Daughter: The Value and Care of Disabled Minds.